LATIHAN STRETCHING PADA LANSIA DI DESA MEKAR SARI KECAMATAN DELITUA KABUPATEN DELI SERDANG - Lili Suryani Tumanggor; Daniel Suranta Ginting (Jurnal Pengabdian Masyarakat Putri Hijau, 2021)
Stretching is a form of exercise therapy aimed at stretching muscles that experience stiffness due to continuous loading when working or it is quite high, and the data is easy to get, doing activities, so that the muscles become stiff, shorten, this triggers pain in the affected muscles. Stretching can overcome problems that often occur, namely neck pain and stiffness, upper and lower back pain, low back pain, pain in the hamstrings and pain in the calves. This health education is carried out to reduce pain by doing stretching. The impact of pain is caused by sensitivity and loss of bodily functions in the lower back. Pain stimuli can be in the form of mechanical, thermal, or chemical stimuli and the mixture is received by the receptors consisting of free nerve endings which have the specification here that an action potential occurs and this impulse is transmitted to the pain center. The treatment for the elderly is to find activities that are suitable for the physical and spiritual abilities of the elderly (stretching), providing nutritious food, encouraging adequate rest, physiological approaches, cognitive approaches. This health counseling is carried out for the elderly with low back pain in Mekar Sari village, Delitua sub-district, Deli Serdang district. The conclusion of this health education is that hip exercises (stretching) in the lower back in the elderly can be a method, which, if done according to the proper procedure, can reduce the level of low back pain in the elderly.